Normalization of Solitude: The Task to Be Done - Idasiak, Michał (Ruch Filozoficzny, 2022)
The pandemic situation showed us, that separation from other people is an important part of our lives and makes even more impact than we thought. Yet, the dominant picture of this separation is hugely negative and was so for a long time. Solitude, being nor positive nor negative on its own, just as being with others, is not something that people as a whole acknowledge in their lives – it is perceived as a state to endure, something that can be useful, but not something we should just live with, at least partially. This paper shows how important it is to create a new picture of solitude – as something normal, not exceptional. It indicates the task to create a new vocabulary around the phenomenon of solitude, free of its negative connotations, which will enable us to incorporate solitude back into our lives. I argue, that such a change in vocabulary may enable us normalization of solitude and that such normalization should be our goal.